PENGARUH CONTEXTUAL TEACHING AND LEARNING (CTL) DAN MEDIA VIDEO TERHADAP MOTIVASI SISWA PADA PELAJARAN FIQH DI MIN MUARA SIBAN PAGAR ALAM - Suwito Suwito (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2020)
Learning fiqh in Islamic elementary schools are often less attractive and tend to be boring for students. In learningfiqh in MI students sought more active and keen to follow the lesson order learning process takes place in a conducive,effective, creative, efficient and fun. CTL approach is appropriate in the eyes pelajaranyang jurisprudence as applicableand can encourage students to live at once untukmengamalkan rules of Islam in daily life coupled with the use of videomedia so hopefully learning fiqh is not boring for students. This study aims to (1. To know the effect of CTL againststudent motivation (2. To Know video media influence on student learning outcomes (3. To know the effect of the CTLand Media Video on the students motivation. The method used in this study is an experimental method that reveal therelationship between two variables or more, or look for the influence of a variable to the other variables through theseexperiments can be obtained from the data on effects of CTL and Media Video on the motivation of the students on thesubjects of fiqh in MIN Muara siban Fences natural. After testing the equality of two average by using t-test result, theexperimental class posttest scores differed significantly from the control class posttest score thitung 3.79> 2.01 ttable to thesignificant level of 5%. This quasi-experimental research results indicate that the effect of CTL and video media in MuaraMIN Siban Pagar Alam on Students’ motivation has proven successful in increasing student motivation.